Submucous implant of abrasive dental materials in rat tongues: clinical and histological evaluation - Pistóia Alexandre Dorneles; Figueiredo Maria Antonia Zancanaro de (Fundação Odontológica de Ribeirão Preto, 2002)
This study evaluated the clinical and histological manifestations produced by the submucuous implant of abrasive dental materials in the rat tongue. A total of 128 rats were divided into 4 groups of 32 rats each, according to the material selected for the implant: Herjos-F prophylactic paste both in its normal composition as well as lacking its abrasive components, SS White pumice stone and the abrasive powder of the 3M finishing and polishing sandpaper. The specimens were submitted to clinical and histological analyses at 30, 60, 90 and 120 days. After 90 days, the formation of nodular lesions in animals implanted with materials containing abrasive substances was observed. Histologically, these materials produced marked chronic granulomatous reactions. Herjos-F prophylactic paste produced the greatest reaction. However, without the abrasive components, this paste caused the mildest tissue reactions, with no inflammatory response, that was seen in a progressively greater number of cases after 90 days.